Multidrug Resistance Modulation Activity of Silybin Derivatives and Their Anti-inflammatory Potential - Dobiasová, Simona; Řehořová, Kateřina; Kučerová, Denisa; Biedermann, David; Káňová, Kristýna; Petrásková, Lucie; Koucká, Kamila; Václavíková, Radka; Valentová, Kateřina; Ruml, Tomáš; Macek, Tomáš; Křen, Vladimír; et al. (Antioxidants, 2020)
Silybin is considered to be the main biologically active component of silymarin. Its oxidized derivative 2,3-dehydrosilybin typically occurs in silymarin in small, but non-negligible amounts (up to 3%). Here, we investigated in detail complex biological activities of silybin and 2,3-dehydrosilybin optical isomers. Antioxidant activities of pure stereomers A and B of silybin and 2,3-dehydrosilybin, as well as their racemic mixtures, were investigated by using oxygen radical absorption capacity (ORAC) and cellular antioxidant activity (CAA) assay. All substances efficiently reduced nitric oxide production and cytokines (TNF-α, IL-6) release in a dose-dependent manner. Multidrug resistance (MDR) modulating potential was evaluated as inhibition of P-glycoprotein (P-gp) ATPase activity and regulation of ATP-binding cassette (ABC) protein expression. All the tested compounds showed strong dose-dependent inhibition of P-gp pump. Moreover, 2,3-dehydrosilybin A (30 µM) displayed the strongest sensitization of doxorubicin-resistant ovarian carcinoma. Despite these significant effects, silybin B was the only compound acting directly upon P-gp in vitro and also downregulating the expression of respective MDR genes. This compound altered the expression of P-glycoprotein (P-gp, ABCB1), multidrug resistance-associated protein 1 (MRP1, ABCC1) and breast cancer resistance protein (BCRP, ABCG2). 2,3-Dehydrosilybin AB exhibited the most effective inhibition of acetylcholinesterase activity. We can clearly postulate that silybin derivatives could serve well as modulators of a cancer drug-resistant phenotype.